2017
DOI: 10.1111/1462-2920.13997
|View full text |Cite
|
Sign up to set email alerts
|

Free‐living chemoautotrophic and particle‐attached heterotrophic prokaryotes dominate microbial assemblages along a pelagic redox gradient

Abstract: Using the anoxic Cariaco Basin as a natural laboratory, particle association of bacterial and archaeal taxa was assessed by iTag sequencing and qPCR gene assays of samples spanning an oxic-anoxic-euxinic gradient. A total of 10%-12% of all bacterial and archaeal cells were found in the particle-associated (PA) fraction, operationally defined as prokaryotes captured on 2.7 µm membranes. Both redox condition and size fraction segregated bacterial taxa. Archaeal taxa varied according to redox conditions, but were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
109
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(122 citation statements)
references
References 113 publications
(180 reference statements)
12
109
1
Order By: Relevance
“…Most of the sulfide, ammonium, and methane input into the system (i.e., via diffusion or in situ production) can be attributed to diffusion from the bottom boundary (91%, 95%, and 97%, respectively), potentially produced near or in the underlying sediments. Our estimates suggest that some hydrogen sulfide is also produced within the water column (depths ∼600–900 m), consistent with the previous detection of sulfate‐reducing bacteria in sinking particles at anoxic depths (Suter et al, ), although some of the apparent sulfide sources may actually be sulfide diffusing out of the sediments on the basin's side walls. The contribution of in situ sulfide sources to overall sulfide fluxes into the redoxcline is relatively small (∼10%) and has decreased in the latter years, based on the estimated ratio of in situ produced versus in situ consumed sulfide.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Most of the sulfide, ammonium, and methane input into the system (i.e., via diffusion or in situ production) can be attributed to diffusion from the bottom boundary (91%, 95%, and 97%, respectively), potentially produced near or in the underlying sediments. Our estimates suggest that some hydrogen sulfide is also produced within the water column (depths ∼600–900 m), consistent with the previous detection of sulfate‐reducing bacteria in sinking particles at anoxic depths (Suter et al, ), although some of the apparent sulfide sources may actually be sulfide diffusing out of the sediments on the basin's side walls. The contribution of in situ sulfide sources to overall sulfide fluxes into the redoxcline is relatively small (∼10%) and has decreased in the latter years, based on the estimated ratio of in situ produced versus in situ consumed sulfide.…”
Section: Resultssupporting
confidence: 90%
“…Given that sulfide oxidation spatially overlaps substantially with nitrate consumption (Figure c), it is probable that nitrate is at least partly used as a terminal electron acceptor for the oxidation of various sulfur compounds, a process observed in other oxygen‐depleted regions of the ocean (Canfield et al, ; Louca et al, ; Rogge et al, ; Schunck et al, ). Indeed, the Gammaproteobacterial clades BS‐GSO2 and SUP05, members of which are frequently implicated in sulfide oxidation and denitrification in oxygen‐poor marine systems (Fuchsman, Murray, & Staley, ; Glaubitz, Kießlich, Meeske, Labrenz, & Jürgens, ; Lavik et al, ; Rogge et al, ; Shah, Chang, & Morris, ; Walsh et al, ), have been observed at high relative abundances in the Cariaco Basin redoxcline (Rodriguez‐Mora et al, ; Suter et al, ; Taylor et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative γ‐proteobacteria S‐oxidizers (GSO) dominating the shallow anoxic and euxinic depths were represented by the SUP05 clade and a single OTU in the Ectothiorhodospiraceae family, closely matching an uncultured Thiorhodospira sp. (Suter et al, ). Related GSOs dominate redoxclines of other oxygen‐depleted environments, such as the Black Sea (Fuchsman et al, ), Baltic Sea (Glaubitz et al, ), shelf water on the Namibian coast (Lavik et al, ), Saanich Inlet (Walsh et al, ), and the Pacific Ocean OMZs (Stewart et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As in many other stratified oxygen-depleted water columns, chemoautotrophic assemblages across the Cariaco's redox transitional zone are comprised of ammonia-oxidizing, nitrite-oxidizing, anaerobic ammonia-oxidizing (anammox), and reduced sulfur-oxidizing microorganisms (Cernadas-Martin et al, 2017;Montes et al, 2013;Suter et al, 2018;Taylor et al, 2001;Wakeham et al, 2012). During the present study's timeframe (2013)(2014)(2015)(2016)(2017), ammonia-oxidizing archaea in marine group I, ammonia-oxidizing betaand γ-proteobacteria, and nitrite-oxidizing Nitrospina (δ-proteobacteria) have been observed across the oxycline (Cernadas-Martin et al, 2017;Suter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%